The HST large programme on ω Centauri – IV. Catalogue of two external fields. Issue 3 (22nd May 2021) - Scalco, M; Bellini, A; Bedin, L R; Anderson, J; Rosati, P; Libralato, M; Salaris, M; Vesperini, E; Nardiello, D; Apai, D; Burgasser, A J; Gerasimov, R
ABSTRACT: In the fourth paper of this series, we present – and publicly release – the state-of-the-art catalogue and atlases for the two remaining parallel fields observed with the Hubble Space Telescope for the large programme on ω Centauri. These two fields are located at ∼12 arcmin from the centre of the globular cluster (in the west and south-west directions) and were imaged in filters from the ultraviolet to the infrared. Both fields were observed at two epochs separated by about 2 yr that were used to derive proper motions and to compute membership probabilities.